Karl Marx al sur: educacion, etica, derchos y tecnologia. - García Ramírez, José Carlos, 1967- (CLACSO, 2021)
Karl Marx to the South is a book that demands our attention, especially at this current historical juncture. José Carlos García presents us with an important work with which he manages to grasp the crucial implications of Marxist thought for Latin America and beyond. For too long, the working class has suffered the ravages of accumulation by dispossession, the growing tentacles of the police state, and technological advances that empower corporations rather than workers. This is a book that talks about the challenges of our time for these times.